2021
DOI: 10.3390/su13095069
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Innovation Areas for Heritage-Led Rural Regeneration: A Multilevel Repository of Best Practices

Abstract: This paper presents the result of the analysis of the data gathered from 20 Role Models (RM) case studies regarding their successful heritage-led rural regeneration models. For the study and comparison of the narratives of these Role Models two tools were used: the Community Capitals Framework, which studied the transference of capitals in each process and the identification of six Systemic Innovation Areas that allow this capital transference. A multilevel repository of best practices has been developed allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Numerous researchers have assessed the cultural heritage potential and its impact on socioeconomic growth of regions or countries, for example, in the context of cultural tourism. Research by Egusquiz et al [55] confirmed the significant contribution of cultural assets and cultural and environmental heritage to economic growth, social inclusion, and environmental sustainability in rural areas, indicating culture as the fourth pillar of sustainable development. The primary goal of the research by Št'astná et al [56] was to determine whether cultural tourism could be a driving force of rural growth.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have assessed the cultural heritage potential and its impact on socioeconomic growth of regions or countries, for example, in the context of cultural tourism. Research by Egusquiz et al [55] confirmed the significant contribution of cultural assets and cultural and environmental heritage to economic growth, social inclusion, and environmental sustainability in rural areas, indicating culture as the fourth pillar of sustainable development. The primary goal of the research by Št'astná et al [56] was to determine whether cultural tourism could be a driving force of rural growth.…”
Section: Discussionmentioning
confidence: 99%
“…: the municipalities of Aalst, Berlare, Bornem, Denderleeuw, Dendermonde, Puurs-Sint-Amands, and Willebroek. Aalst (86,445 inhabitants) and Dendermonde (45,769 inhabitants) are modestly sized cities, while Puurs-Sint-Amands (25,882), Bornem (21,366), Berlare (14,958), Denderleeuw (20,338), and Willebroek (26,462) are more rural communities in the urban fringe. These municipalities are part of the larger tourist region of Scheldeland.…”
Section: Study Areamentioning
confidence: 99%
“…Changes on the demand side-following the general shift toward an experience and transformative economy-have also seen a growth in experience-oriented tourists, who increasingly seek to immerse themselves in authentic local life and its environment, creating new opportunities for less-traveled destinations [12,13]. Analyzing 20 role models, Egusquiza and colleagues [14] identified different successful, heritage-led rural regeneration models and found that among 33 key resources, the natural landscape, historic assets, and traditions were the main drivers of regeneration processes, ultimately leading to increased jobs and revenues, a more sustainable tourism sector, and improvements in well-being. It was further noted that how, apart from the link between tourism, conservation, and rural regeneration, tourism in natural areas has been seen to increase the physical and mental well-being of visitors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Participatory planning can be problematic in rural areas, due to the loss of local knowledge and disengagement [28], as well as due to the geography and the infrastructure of the place, and the relevant "communities of interest" that can be hard to sustain over time [29]. At the same time, community and stakeholder involvement is crucial for undertaking inclusive and sustainable rural regeneration, because it is able to generate additional benefits not just to the social capital, but also to the natural, built and human capitals of the territory [30].…”
Section: Introductionmentioning
confidence: 99%